Giant thrombosed aneurysm of P2 anterior segment of left posterior cerebral artery: Case Report and review of literature - Sharma, Gopal Raman; Joshi, Sumit; K C, Raj Kumar; Bhattachan, Maya; Bhandari, Pawan Kumar (Nepal Journal of Neuroscience, 2017)
P2A (anterior) segment aneurysm of posterior cerebral artery is one of the rare aneurysm of posterior circulation. We report a case of 30 years old right handed young man who presented with features of SAH in Emergency Department and cerebral angiogram confirmed left posterior cerebral artery P2A segment thrombosedfusi form aneurysm. Postoperative recovery was good except left sided ptosis after microsurgical trapping via left temporal approach. Treatment modality and outcome after intervention for P2A segment aneurysm will be discussed. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, Page : 42-45